Synopsis, Is there fiscal space for CAADP in Ghana? - Younger, Stephen D. (International Food Policy Research Institute, 2015)
In 2009, Ghana was one of the first African countries to accept the Comprehensive Africa Agriculture Development Programme (CAADP) target of committing ten percent of government expenditure to agriculture. Despite this commitment, Ghana remains far short of that goal. In recent years, spending on agriculture has increased, but only to about 3.5 percent of total expenditures (Benin 2014; ReSAKSS 2015). To attain the CAADP target, Ghana needs to spend an additional 6.5 percent of total expenditures, or about 2 percent of GDP, on agriculture. Yet Ghana also finds itself needing to reduce an historically large and persistent budget deficit of about ten percent of GDP. In such difficult fiscal times, is it possible for Ghana to meet its CAADP commitment?